Psychological possibilities of the manifestation of musical abilities in students (Eurasian Journal of Learning and Academic Teaching, 2023)
This article delves into the psychological dimensions of musical abilities in students and investigates effective methods for nurturing and harnessing these talents. We explore the various facets of musical aptitude, the methodologies employed to identify and enhance these abilities, and the potential long-term benefits for students' cognitive, emotional, and social development